2022
DOI: 10.15420/cfr.2022.17
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in Women with Heart Failure: Sex-specific Characteristics and Current Challenges

Abstract: Cardiovascular disease (CVD) represents a significant threat to women’s health. Heart failure (HF) is one CVD that still has an increasing incidence and about half of all cases involve women. HF is characterised by strong sex-specific features in aetiology, clinical manifestation and outcomes. Women are more likely to have hypertensive heart disease and HF with preserved ejection fraction, they experience worse quality of life but have a better overall survival rate. Women’s hearts also have unique morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 144 publications
0
7
0
Order By: Relevance
“…Women are less likely to be referred for specialist HF care 6 or to receive optimized guideline therapy 7 , 8 and, as a result, report lower quality of life independent of EF or natriuretic peptide level. 8 , 9 Sex-specific differences in cardiac imaging 10 and circulating biomarkers have previously been described. 11 …”
Section: Introductionmentioning
confidence: 95%
“…Women are less likely to be referred for specialist HF care 6 or to receive optimized guideline therapy 7 , 8 and, as a result, report lower quality of life independent of EF or natriuretic peptide level. 8 , 9 Sex-specific differences in cardiac imaging 10 and circulating biomarkers have previously been described. 11 …”
Section: Introductionmentioning
confidence: 95%
“…One example is a recent review that discusses the clinical and morphological differences found with imaging in women compared to men as they are being evaluated for heart failure. 6 The review points out that women have smaller heart volumes even when factored for body surface area or mass, and women have higher median left ventricular ejection fraction. 6 In addition, women have a lower degree of left ventricular hypertrophy than men at all stages of ventricular dysfunction.…”
Section: Editorialmentioning
confidence: 99%
“…6 The review points out that women have smaller heart volumes even when factored for body surface area or mass, and women have higher median left ventricular ejection fraction. 6 In addition, women have a lower degree of left ventricular hypertrophy than men at all stages of ventricular dysfunction. 6 These differences are likely due to genetic or chromosomal differences rather than differences in sex steroids, since these differences do not change following menopause.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although overall survival rates are better in women, women suffer with higher morbidity as evidenced by higher rates of hospitalization and worse quality of life. [2][3][4][5] Several anatomical differences have been discovered in women's hearts, affecting both systolic and diastolic cardiac physiology. Women also have sex-specific etiologies of heart failure and unique manifestations in genetic-related cardiomyopathies (Figure 1).…”
Section: Introductionmentioning
confidence: 99%